2015
DOI: 10.3389/fphar.2014.00291
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 is critically involved in placentation, spiral artery remodeling, and blood pressure regulation during murine pregnancy

Abstract: The onset of pregnancy implies the appearance of a new organ, the placenta. One main function of the placenta is to supply oxygen to the fetus via hemoproteins. In this review, we highlight the importance of the enzyme heme oxygenase-1 (HO-1) for pregnancy to be established and maintained. HO-1 expression is pivotal to promote placental function and fetal development, thus determining the success of pregnancy. The deletion of the gene Hmox1 in mice leads to inadequate remodeling of spiral arteries and suboptim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 91 publications
(177 reference statements)
3
41
0
Order By: Relevance
“…Glucose regulates the Heme oxygenase-1 that is a central player for immune regulation. 44 Furthermore, glucose regulates the exosomal signaling by placental cells and the release of cytokines. 45 It might be that a dysregulation in glucose metabolism at first trimester in pregnancies has adverse outcome on the CD74 expression and therefore associates with placental insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose regulates the Heme oxygenase-1 that is a central player for immune regulation. 44 Furthermore, glucose regulates the exosomal signaling by placental cells and the release of cytokines. 45 It might be that a dysregulation in glucose metabolism at first trimester in pregnancies has adverse outcome on the CD74 expression and therefore associates with placental insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed decreased placenta size and weight, as well as impaired cell viability in mice heterozygous ( Hmox1 +/− ) for HO‐1 . Along these lines, it has been shown that both Hmox1 +/− and Hmox1 −/− mice show an impairment in uterine natural killer (uNK) ‐dependent maternal spiral arteries remodeling during implantation because of reduced numbers of uNK . Interestingly, treatement of Hmox1 +/− mice with low doses of CO improved both uNK proliferation, spiral arteries remodelling and also stabilized blood presure, suggesting that this gas plays a key role during uNK‐dependent intrauterine growth .…”
Section: The Ho‐1–co System Reduces Pathologies Caused By the Immune mentioning
confidence: 96%
“…141,142 Along these lines, it has been shown that both Hmox1 +/À and Hmox1 À/À mice show an impairment in uterine natural killer (uNK) -dependent maternal spiral arteries remodeling during implantation because of reduced numbers of uNK. 143,144 Interestingly, treatement of Hmox1 +/À mice with low doses of CO improved both uNK proliferation, spiral arteries remodelling and also stabilized blood presure, suggesting that this gas plays a key role during uNK-dependent intrauterine growth. 143,144 Similar data were obtained in a trophoblastic stem cell line that resembles the development of trophoblasts into giant cells, which showed that HO-1 inhibition compromises cell viability and their ability to differentiate.…”
Section: Ho-1 Reduces Innate Immunity-mediated Inflammatory Diseasesmentioning
confidence: 98%
“…In mouse models where HO-1 is genetically deleted, there is inadequate remodeling of the spiral arteries, diminished numbers of uterine natural killer cells at the maternal fetal interface, and fetal growth restriction. [33][34][35] Furthermore, mothers carrying an HO-1 +/− heterozygote develop hypertension in the latter stages of their pregnancy. 34 However, whether these intriguing findings are relevant to early human placentation is yet to be proven.…”
mentioning
confidence: 99%